Relationships between Anxiety, Emotional Intelligence, and Motivational Climate among Adolescent Football Players - Manuel Castro-Sánchez; Félix Zurita-Ortega; José Luis Ubago-Jiménez; Gabriel González-Valero; Eduardo García-Mármol; Ramón Chacón-Cuberos (MDPI AG, 2019)
Background: Emotional and motivational factors are fundamental in the context of sport, as they directly relate to sports performance and anxiety. Methods: The present study aimed to analyze the relationships between motivational climate (MC), emotional intelligence (EI), and anxiety within a sample of footballers playing at a low level. The sample was composed of 282 registered football players aged between 16 and 18 years old (16.96 ± 0.77), playing in the lower tier in the province of Jaen (Spain). Data were self-reported, with participants responding to the Perceived Motivational Climate in Sport Questionnaire (PMCSQ-2), the Schutte Self-Report Inventory (SSRI), and the State Trait Anxiety Inventory (STAI). Results: The results showed that footballers who reported higher levels of state anxiety and trait anxiety also demonstrated lower EI and more negatively perceived and regulated their emotions. Moreover, an ego-oriented climate was associated with higher levels of anxiety, while a task-oriented climate was related to lower levels of anxiety and higher levels of EI. No relationship was identified between the emotional aspects of young footballers and holding a motivational orientation toward an ego climate. Conclusions: Football players who more greatly perceived a task-oriented climate had higher EI and usually reported lower levels of anxiety related to sport performance. It is therefore important to promote intrinsic motivations and develop the capacity of footballers to regulate their own emotions.